PENGARUH PENGELUARAN PEMERINTAH, INVESTASI SWASTA TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI KOTA SINGKAWANG - B 611 11007, Romawi Marthin (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT Title of researchis the influence of local government spending on regional economic growth and welfare in the region Singbebas. Districts/cities in the region Singbebas similiar phenomena in several ways, such as public expenditure, economic growth, income, and IPM. But with the enactment of Law No.32 and. 33 in 2004, the decentralization of development in local government. This condition is expected to be momentum for the community and the government to correct past deficencies. Policies that can be done through a policy of local government spending. APBD require attention in terms of budget distribution, so as to stimulate the creation of new sources of revenue for the region, economic growth and others that will eventually affect directly or indirectly on the welfare of the community. Research problem is how to influence local government spending on regional economic growth and walfare in the region Singbebas, while the goal is to assessthe influence of local government spending on regional economic growth and walfare, as well assess the effect of economic growth on the welfare of the community in the district/ city areas Singbebas. The study uses descriptive and verification method an data that are time series in 2005 unitil 2009. To see the effects, the data were processed using regression analysis and pass the test of Classical Assumptions. Based on analysis, it turn out that local government spending increased sharply each year is not followed by significant economic growth and improved welfare of the community. The building orientation is not completely lead to public service but rather the operational stability of governance. Regression accept Ho, namely regional spending (X) no significant effect on economic growth (Y1) and social welfare (Y2). Similarly, economic growth (Y1), no significant effect on the welfare of society (Y2). Regression line has a positive relationship. Keywords : Local government Expenditure